Body image, dysfunctional attitudes, and depression in aesthetic surgery patients [Estetik cerrahi hastalarinda beden imaji, isleVsel olmayan tutumlar Ve depresyon] - (:unkn) unknown (Turkish Society of Plastic Reconstructive, and Aesthetic Surgery, 2014)
Nowadays, the rate of seeking aesthetic surgery is ever increasing. The importance of conducting psychosocial evaluation of the patients as well as evaluating physical health status during the perioperative period has been emphasized. The aim of the present study is to examine body image, dysfunctional attitudes, and depression in aesthetic surgery patients during the preoperative period. The study design was cross-sectional, descriptive, and correlational. Data was collected during July 1st - September 1st, 2011 from 139 patients who presented at the aesthetic surgery clinic of two private hospitals, were admitted to the hospital for elective aesthetic surgery, and accepted to participate in the study. The Information Form, the Multidimensional Body-Self Relations Questionnaire (MBSRQ), the Dysfunctional Attitude Scale (DAS), and the Beck Depression Inventory (BDI) were administered to the patients. The mean MBSRQ score of the patients was 205.31±25.42, the mean DAS score was 180.97±29.62, and the mean BDI score was 7.28±6.9. It was determined that there were significant correlations between the MBSRQ total score, the MBSRQ subscale scores, dysfunctional attitudes, and the BDI score. The health orientation subscale scores showed significant differences according to gender. It was determined that body image was related to dysfunctional attitudes and depressive symptoms in aesthetic surgery patients during the preoperative period. Gender and age affect some dimensions of body image in these patients. In the light of our results, it can be said that determining body image, dysfunctional attitudes, and depressive symptoms while conducting the psychosocial evaluation of patients during the preoperative period may play a significant role in preventing possible complications and clarifying expectations.
Keywords: Aesthetic surgery; Body image; Depression; Dysfunctional attitudes